Implementing Big Ball Games to Enhance Coordination in 11–12-Year-Old Students: A Gender-Based Analysis - Safitri, Aziza Puspadewi; Kriswanto, Erwin Setyo; Pambudi, Aris Fajar; Prabowo, Trisnar Adi (Physical Education Theory and Methodology, 2025)
Background. The development of coordination during childhood, particularly between the ages of 11 and 12, plays a critical role in overall well-being and long-term physical development. Big ball games have been recognized as an effective medium to improve coordination. However, these games often emphasize basic technical skills, with limited scientific evidence exploring whether gender moderates the effect of big ball games on coordination outcomes. Objectives. This study’s primary objective was to evaluate the impact of big ball games on coordination development in 11–12-year-old students, with consideration of gender differences. Materials and Methods. A quasi-experimental research design with a pretest–posttest approach was employed. Participants included 40 students: 20 male students (age: 11.5 ± 0.3 years; height: 148.9 ± 3.0 cm; weight: 44.6 ± 2.5 kg), and 20 female students (age: 11.4 ± 0.2 years; height: 145.7 ± 1.3 cm; weight: 40.0 ± 1.1 kg). Samples with known initial pretest scores were divided using ordinal pairing with the A-B-B-A formula and then grouped into the experimental group (EG) and the control group (CG). The intervention consisted of five big ball game models delivered over six weeks (18 sessions), with three sessions per week held from 7:00 to 9:00 AM. Intensity monitoring for this game was 65% - 75% or rating of perceived exertion (RPE) at level 12 - 14 (moderate). Coordination was assessed using the Alternate Hand Wall Toss Test (AHWT), a validated tool for evaluating hand-eye coordination. Data were analyzed using MANOVA via SPSS version 26. Results. MANOVA analysis showed a significant effect between gender (p < 0.05) and EG (p < 0.05) on coordination. Meanwhile, interaction between the two did not determine a substantial effect multivariately (p > 0.05). The results of the Univariate Test revealed that gender had a significant influence on the improvement of coordination (F = 85.652, p < 0.001, η²ₚ = 0.704), which shows that 70.4% of the variation in coordination enhancement is explained by gender differences. Subsequently, based on the treatment (EG and CG) on student coordination (F = 147.366, p < 0.001, η²ₚ = 0.804), it was demonstrated that 80.4% of the variation in coordination is explained by differences in treatment. Between-Subjects Effect Test indicated that in pretest stage there was no difference in coordination between EG and CG (p = 0.600), while in posttest stage there was a significant difference (p = 0.000). In addition, a marked interaction was found between gender and group in posttest stage (p = 0.048). Conclusions. The structured, engaging, and consistent application of big ball games significantly enhances coordination in children aged 11–12 years, with pronounced effects in the experimental groups. These findings underscore the influence of physiological and psychological factors on coordination development, highlighting gender-based differences in responsiveness to physical activity interventions. Therefore, physical education programs should adopt inclusive game-based approaches that consider gender-specific needs to maximize coordination development in all students.